Colonization, territorial dispossession and capitalist modernization in the Fütawillimapu - Fuentes, Alejandro (2026)
Based on a historical analysis, this article analyzes the loss of autonomy, colonization and territorial dispossession of the Mapuche Williche people in the Fütawillimapu. A process that began to take shape with the signing of the Tratado de las Canoas in 1793, to later begin with a gradual process of land dispossession by the Spanish Crown and later by the nascent state of Chile. The latter supported the «German colonization» with the idea of opening and expanding foreign trade, this accelerated the modernization and agro-livestock production of capitalist cut, and with that the emergence of a new economic-political elite and the process of land usurpation accelerated by means of violence and other practices to expand the economic area. Thus began a process of modernization and agro-livestock production in the region at the end of the 19th century and beginning of the 20th century.